1968
DOI: 10.1111/j.1476-5381.1968.tb08484.x
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the histidine‐histamine relationship in vivo: effects of endotoxin and of histidine decarboxylase inhibitors

Abstract: . Mice were injected with (14C)‐l‐histidine, killed at various intervals, and tissues assayed for (14C)‐histamine. In some cases free (14C)‐l‐histidine and total (14C) were also determined. . Removal of stomach, the most active histamine‐forming tissue, failed to reduce the (14C)‐histamine content of any tested tissue; (14C)‐histamine concentrations in lung and muscle of gastrectomized mice were higher than in sham‐operated controls. . In mice pretreated with endotoxin and subsequently injected with (14C)‐l‐hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Animals were sacrificed post-14C-L-histidine at 5 minutes in stomach experiments, and 3 days in skin experiments; the 3 day interval was to permit dissipation of loosely bound a4C-histamine so that mast cell 14C-histamine of skin was measured. These intervals are in accordance with our previous tests [5]. For brain tests, animals were sacrificed 25-40 minutes posthistidine unless a shorter interval was required by experimental conditions (exp.…”
Section: Animal Experimentationmentioning
confidence: 91%
See 2 more Smart Citations
“…Animals were sacrificed post-14C-L-histidine at 5 minutes in stomach experiments, and 3 days in skin experiments; the 3 day interval was to permit dissipation of loosely bound a4C-histamine so that mast cell 14C-histamine of skin was measured. These intervals are in accordance with our previous tests [5]. For brain tests, animals were sacrificed 25-40 minutes posthistidine unless a shorter interval was required by experimental conditions (exp.…”
Section: Animal Experimentationmentioning
confidence: 91%
“…However, when decaborane-treated mice were injected with 14C-L-histidine, stomach 14C-histamine content was significantly higher than for controls [10]. A similar in vivo test was made on rats; ~-HH, a strong inhibitor of histidine decarboxylase [5] was also tested. Two groups of rats, 111 g average weight, were injected with vegetable oil, and one group with decarborane 1.5 mg in oil; all were fasted for the duration of the experiment.…”
Section: Stomach Experiments Experiments 9 Decaborane Inhibits Hisfidinementioning
confidence: 93%
See 1 more Smart Citation
“…This is a view originally suggested by Schayer (1960a, b). It is perhaps unlikely that the increased tissue histamine levels are the result of a reduced ability to destroy histamine since it has been reported that endotoxin has no effect on diamine oxidase activity or on histamine methylation (Reilly & Schayer, 1968;1970).…”
Section: The Role Of Histamine In Endotoxin Shockmentioning
confidence: 99%
“…With improved means for investigating histamine formation and catabolism in vivo (Reilly & Schayer, 1968a, 1968b, 1970, 1971a, 1971b we have extended studies to mice.…”
Section: Introductionmentioning
confidence: 99%